2001
DOI: 10.1046/j.1540-8167.2001.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Prediction of Abnormal Genotype in Congenital Long QT Syndrome: Experience in 101 Related Family Members

Abstract: Even in this homogeneous LQTS population, the phenotype was so variable that clinical and detailed ECG analyses did not permit an accurate diagnosis of gene carrier status, especially in children. Sustained microvolt TWA was a specific (100%) but insensitive (18%) marker for LQTS. Its ability to predict risk of arrhythmia in this population remains to be determined. Genetic testing serves an essential role in screening for carriers of LQTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 26 publications
(6 reference statements)
1
49
0
Order By: Relevance
“…6 Overt T-wave alternansgrossly visible beat-to-beat variation in T-wave amplitude and/or polarity-is viewed as an important prognostic indicator for TdP and sudden cardiac death in LQTS patients, but appears less frequently (2.5% to 7% of LQTS study participant samples) than microvoltage T-wave alternans (identifiable only by special signal processing-18 to 45% of LQTS patient groups undergoing specialized testing). 48 Another repolarization parameter, QT dispersion-the difference between the maximum and minimum QT values across the 12 standard ECG leads-has led to inconsistent results in distinguishing symptomatic from asymptomatic patient groups and fails to take into account T-wave morphology. 49 …”
Section: Clinical Evaluation and Laboratory Testing Phenotypic Ascertmentioning
confidence: 99%
“…6 Overt T-wave alternansgrossly visible beat-to-beat variation in T-wave amplitude and/or polarity-is viewed as an important prognostic indicator for TdP and sudden cardiac death in LQTS patients, but appears less frequently (2.5% to 7% of LQTS study participant samples) than microvoltage T-wave alternans (identifiable only by special signal processing-18 to 45% of LQTS patient groups undergoing specialized testing). 48 Another repolarization parameter, QT dispersion-the difference between the maximum and minimum QT values across the 12 standard ECG leads-has led to inconsistent results in distinguishing symptomatic from asymptomatic patient groups and fails to take into account T-wave morphology. 49 …”
Section: Clinical Evaluation and Laboratory Testing Phenotypic Ascertmentioning
confidence: 99%
“…For 20 years, an LQT2 family has been studied extensively by our multidisciplinary group (14,15). Initial genotype testing of living family members following the sudden death of a 31-year-old female with a history of syncope along with the subsequent LQT2 diagnosis in a paternal aunt revealed a C→T nucleotide substitution at position 2,254 in exon 9 of KCNH2 resulting in the hERG R752W missense mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a study performed on this large Cleveland LQT2 family carrying the hERG R752W mutation demonstrated that even in this homogeneous LQTS population, the phenotype was so variable that detailed clinical and ECG analyses did not permit an accurate diagnosis of gene carrier status. In fact, there was substantial overlap (78%) of QTc among subjects with and without the mutation, suggesting the presence of 1 or more modifier genes (14). We deployed a novel strategy combining the use of patient-derived iPSC-CMs alongside exome sequencing and genome editing to unravel novel electrophysiological arrhythmogenic mechanisms and identify new Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty primary studies 28,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] reported sensitivity and specificity estimates by using ECG to detect LQTS and/or HCM,…”
Section: Characteristics Of Reviewed Studiesmentioning
confidence: 99%
“…13 When incorporating Kobza, the summary prevalence increased fivefold to 38 per 100 000 (95% CI: 19-58) and heterogeneity increased (I 2 = 99%, P , .001). [42][43][44][45][46][47][48][49][50] The Bayesian sensitivity analysis giving the Schwartz 13 prior a low weight (1/2500) resulted in similar 48 Genotyped probands and relatives Not specified To provide clinical context, we used the summary phenotypic prevalence estimate for LQTS and 2 illustrative points (the maximal accuracy point and the maximal specificity point) on the HSROC curve for detection of LQTS by using ECG (Table 3). For both points, the NPV was near 100%.…”
Section: Long Qt Syndromementioning
confidence: 99%